HOW POLICY SHAPES INVESTMENT OPPORTUNITIES? COMPARATIVE INSIGHTS FROM ASIA AND AFRICA - Abu Bakarr S Turay; Ali Maksum; Dauda Alusine Kuyateh (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
During President Trump's first term, he declared a US-China trade war, which formed numerous opportunities for developing countries. It also urges multinational corporations to relocate their manufacturing factories outside of the US-China region to prevent further increasing tariff. This study used "the dependency theory" to understand that Indonesia is the biggest economy in ASEAN, despite Nigeria and South Africa as the largest economies in Africa.  As Sierra Leone's geographical position connects South America, Africa, and Asia by Sea, but they did not have any significant advantages during the trade war, in comparison to Vietnam. Therefore, this study compares and analyzes two forms of policy competition, Incentives-Based (IBC) and Rules-Based (RBC), to solve the issue of how these Global South nations should benefit from the Trump tariff war. Using qualitative and quantitative methods, it examines the opportunities for the tariff wars ahead between developed countries, which may lead to another great recession. As the results, this study shows that policies do not accommodate to investors as those in Vietnam, whose population is smaller than Indonesia's. Obviously, Nigeria is serving as an alternative for investment, increasing its GDP and creating a favorable public perception of free trade.